Discontinuous yield behavior in titanium alloys caused by activated dislocations during tensile testing at room temperature. (1st July 2023) - Sun, Shichen; Fang, Hongze; Chen, Ruirun; Li, Yili; Su, Yanqing; Guo, Jingjie
Abstract: Discontinuous yield (DY) in titanium alloys at room temperature is revealed for the first time, showing its importance for formulating the deformation process. Titanium alloys with different contents of the β phase and morphology of the α phase were prepared by adding vanadium, and the DY behavior during tensile testing at room temperature was analyzed. The results show that DY is caused by dislocation slip in the primary α (αp ) phase excited by the accumulation of dislocations at the αp /β phase interface. When the V content increases, the content of β phase increases from 17 to 53.4% and the aspect ratio of αp phase decreases from 10.1 to 4.3. The difference of hardness and Young's modulus between β and αp phases increases from 0.08 to 1.39 GPa and 11.18 to 25.72 GPa, respectively. These changes induce the increase of local dislocation density, which leads to DY. Graphical abstract: Image, graphical abstract